Analytical Framework for Coordinated Planning and Operation of Multicarrier Energy Systems - Di Somma, Marialaura; Papadimitriou, Christina; Rousis, Anastasios Oulis; Patsidis, Angelos; Shafie‐Khah, Miadreza; Shahbazbegian, Vahid; Askeland, Magnus (Wiley-VCH GmbH, 2024)
Local multicarrier energy systems (MCESs) offer a unique opportunity to exploit the synergies from the interplay of multiple energy carriers and utilize local renewables, thus increasing energy efficiency and supply reliability as well as reducing dependencies from the external networks. To make them sustainable not only from the energy and environmental perspective but also from the economic one and have a concrete option to the centralized energy systems based on fossil fuels, coordinated planning and operation on multiple time horizons is extremely important. This chapter covers all the transversal aspects related to this issue, by presenting a detailed analytical framework for the optimal design and operation of MCESs. First, the chapter presents the modeling of a wide range of generation, conversion, and storage technologies that can be part of MCESs. Then, the optimization frameworks for the design and the operation problems are established, by presenting several types of objective functions, constraints, and solution methodologies. The analytical frameworks are structured by covering different time horizons from long-term system planning to day-ahead and real-time operation. The effectiveness of the tools proposed to address each of these phases will be proved with a proper case study and discussion of simulation results. In addition, a critical overview of the current commercial tools available for the optimal design and operation of MCESs will be presented, by mapping them according to several criteria such as type, type of users, coverage of multicarrier aspects, objective functions, functionalities, mathematical approach, temporal resolution, and time horizons as well as pros and cons in their application to MCESs.
Keywords: multicarrier energy systems; optimal planning; optimal operation; mathematical programming; optimization tools; fi=Sähkötekniikka|en=Electrical Engineering|